Strategies for Navigating Barriers Faced by Women in the Finnish Startup Ecosystem - Tamminen, Nelli (My University, 2026)
Finland ranks highly in international comparisons of gender equality, yet the startup ecosystem remains male-dominated. There are relatively few women founders and women in decision-making positions, and funding is distributed unevenly. This study examines how women in the Finnish startup ecosystem experience and interpret barriers to entrepre-neurship, how they navigate them, and which individual and structural strategies support them. The study is situated within the field of feminist entrepreneurship research. The study builds on a conceptual framework developed through an extensive literature review on the challenges women face in the field of entrepreneurship. It was conducted as a qualitative multiple-case study. The data consist of nine interviews with women founders and female ecosystem actors who have experience with investors, accelerators, gatekeepers, and networks. The material was analysed using the Gioia methodology. The findings show that women’s pathways into startup entrepreneurship are shaped by late and often accidental exposure, gendered educational and career pipelines, and early messages about who entrepreneurship is for. Barriers do not appear as separate issues but as tightly intertwined external, internal, relational, and structural factors. A masculine founder norm, informal “good guy” networks, credibility gaps, experiences of safety concerns and harassment, and welfare-state benefit and care arrangements together form a context in which the opportunity cost of startup entrepreneurship is high for women. At the same time, the study shows that women are not merely objects of structural forces but active agents. They seek support and peer sparring, draw on mentors and investor networks, build and perform their competence, act as role models, create safer spaces, and refuse to collaborate with actors who cross boundaries. The study challenges the notion of the startup ecosystem as a neutral meritocracy and highlights that a more gender-equal ecosystem requires both individual-level support structures and better alignment of social security, care arrangements, and funding systems with entrepreneurship.

Suomi sijoittuu kansainvälisissä vertailuissa korkealle sukupuolten tasa-arvossa, mutta startup-ekosysteemi on edelleen miesvaltainen. Naispuolisia yritysten perustajia ja naispuolisia päättäjiä on vähän, ja rahoitus jakautuu epätasaisesti. Tämä tutkimus tarkastelee, miten naiset suomalaisessa startup-ekosysteemissä kokevat ja tulkitsevat yrittäjyyteen liittyviä esteitä, miten he navigoivat niitä sekä millaiset yksilölliset ja rakenteelliset strategiat tukevat heitä. Tutkimus sijoittuu feministisen yrittäjyyden tutkimuskenttään. Tutkimus rakentuu viitekehykselle, joka on koostettu laajasta kirjallisuuskatsauksesta, jossa tarkastellaan naisten kohtaamia haasteita yrittäjyyden kentällä. Tutkimus toteutettiin laadullisena monitapaustutkimuksena. Aineisto koostuu yhdeksästä haastattelusta, joissa haastateltiin naisperustajia ja naispuolisia ekosysteemitoimijoita, joilla on kokemusta sijoittajista, kiihdyttämöistä, portinvartijoista ja verkostoista. Aineisto analysoitiin Gioia-menetelmää hyödyntäen. Tulokset osoittavat, että naisten polut startup-yrittäjyyteen rakentuvat myöhäisten ja sattumanvaraisten altistumisten, sukupuolittuneiden koulutus- ja uraputkien sekä varhaisten viestien varaan siitä, kenelle yrittäjyys kuuluu. Esteet eivät näyttäydy erillisinä ongelmina vaan tiiviisti toisiinsa kietoutuneina ulkoisina, sisäisinä, relationaalisina ja rakenteellisina tekijöinä. Maskuliinisten yrittäjien normi, epäviralliset ”good guy”-verkostot, uskottavuus-vaje, turvallisuus- ja häirintäkokemukset sekä hyvinvointivaltion etuus- ja hoivajärjestelmät muodostavat kokonaisuuden, jossa naisille startup-yrittäjyyden vaihtoehtoiskustannus on korkea. Samalla tutkimus osoittaa, että naiset eivät ole vain rakenteiden kohteita, vaan aktiivisia toimijoita. He hakevat tukea ja vertaissparrausta, hyödyntävät mentoreita ja sijoittajaverkostoja, rakentavat ja esittävät osaamistaan, toimivat roolimalleina, luovat turvallisempia tiloja ja kieltäytyvät yhteistyöstä rajat ylittävien toimijoiden kanssa. Tutkimus haastaa käsityksen startup-ekosysteemistä neutraalina meritokratiana ja korostaa, että tasa-arvoisempi ekosysteemi edellyttää sekä yksilötason tukirakenteita että sosiaaliturvan, hoivan ja rahoitusjärjestelmien parempaa yhteensovittamista yrittäjyyden kanssa.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development